Trauma Informed Interventions and Academic Adjustment among Adolescent Students in Public Secondary Schools in Kenya - Omare, Justine Momanyi; Onderi, Peter Omae; Bashaija, Athanansio (Utan Kayu Publishing, 2023)
Globally, the problem of escalating incidences of trauma among adolescents has adversely affected their physical, behavioral, emotional and psychological functioning hence impairing their quality and ability to adjust in school. The purpose of this study was to establish the effectiveness of trauma informed interventions and academic adjustment among adolescents in public secondary schools in Kisii County. This study employed an explanatory sequential mixed method design. The study targeted a population of 1100 students from which 275 students were sampled through simple random and purposive sampling technique. Data were collected using self-administered questionnaires, Focused Group Discussions, in-depth interviews and academic adjustment scale. Both descriptive and inferential techniques were employed to analyze quantitative data. The qualitative data were analyzed thematically. The results from Pearson Correlation coefficient affirmed a positive statistically significant nexus (n=.732, n= 275, p<.0.05) between trauma informed interventions and academic adjustment. The qualitative data findings further affirmed that trauma informed interventions enhance academic adjustment and resilience among adolescents. The study concluded that effective adoption of trauma informed interventions are critical in coping with academic adjustment levels among adolescents.